SURVEI PEMBELAJARAN MENULIS TEKS BERITA SEBAGAI REFLEKSI LITERASI MEMBACA SISWA - Sastromiharjo, Andoyo; Mulyati, Yeti; Dewi Pramesti, Utami; S.Anshori, Dadang (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This article describes the comparison of news-writing learning during offline learning and online learning with the aim of getting a portrait of news-writing learning in both types of learning. Research conducted is descriptive quantitative. The research sample was Junior High School teachers in all regions of Indonesia who were randomly selected. The questionnaire is an instrument in this studywhich is distributed via google form. The research steps were as follows: (1) determining the topic; (2) exploring theoretical studies; (3) formulating instruments; (4) validating the instrument; (5) disseminating instruments; (6) collecting and calculating the results of the questionnaire that has been obtained; (7) discussing and concluding the research results. The results of research on both types of learning show several similarities and differences. The findings that contain the similarities between offline and online learning are: (1) more than 50% of the teachers did not use certain learning models for news writing materials; (2) that audiovisual media is the most widely used (50-51.8%); (3) news text is the final product of learning more than 50%; and (4) performance assessment used 50-56.1%. The resulting differences are: (1) offline learning does not use applications, while applications that are widely used online are the WA Group (48.6%); (2) the most prominent learning methods and techniques used when offline were discussion (48.2%), while online was direct observation (35.7%).